2014
DOI: 10.1021/ma501015s
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Interactions of Polystyrene and Fullerenes in Dilute to Semidilute Solutions

Abstract: We report the polymer conformation and fullerene aggregation in a ternary system containing polystyrene, C 60 and toluene measured by small angle neutron, static and dynamic light scattering. We investigate polymer concentrations across the dilute and semidilute regime for five polymer molecular weights (M w =20k-1Mg/mol), and fullerene concentrations below and above its miscibility threshold in toluene.We find that the polymer radius of gyration (R poly g ), hydrodynamic radius (R h ) * To whom correspondence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(78 reference statements)
2
9
0
Order By: Relevance
“…We examined the ternary solution phase behaviour of a model PS/C 60 /toluene mixture to elucidate the effect of addition of a polymer to the miscibility of C 60 , as well as the effect of C 60 on the polymer conformation. As we have shown previously 5 and corroborated with this work, the conformation of PS remains unperturbed across the dilute and semi-dilute regimes. By contrast, the addition of PS to C 60 /toluene solutions linearly decreases the miscibility limit of C 60 in the mixture compared to that in neat toluene.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We examined the ternary solution phase behaviour of a model PS/C 60 /toluene mixture to elucidate the effect of addition of a polymer to the miscibility of C 60 , as well as the effect of C 60 on the polymer conformation. As we have shown previously 5 and corroborated with this work, the conformation of PS remains unperturbed across the dilute and semi-dilute regimes. By contrast, the addition of PS to C 60 /toluene solutions linearly decreases the miscibility limit of C 60 in the mixture compared to that in neat toluene.…”
Section: Discussionsupporting
confidence: 92%
“…1a which we have found to correspond to fullerene clusters. 5 SLS was used to probe C 60 cluster formation by polymer addition in solution and thus gauge solution miscibility. We rst measured the exact fullerene solubility limit for our C 60 grade in toluene by stirring solutions of various concentrations for 48 h, in the absence of light, at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…into account the fact that the neutron SLD of fullerenes is very different from that of protonated toluene, but close to that of deuterated toluene[46], we may conclude that the replacement of the initial protonated toluene guest in the deuterated sPS crystalline region by the subsequently loaded fullerenes took place to a very small extent only, since the scattering features characteristic of the crystalline lattice were not affected apparently. Otherwise, the 010 reflections should have been reduced drastically, as in the case of using deuterated toluene as guest in the sPS co-crystals.…”
mentioning
confidence: 75%
“…Previous studies on the model ternary system polystyrene, C60 fullerene and toluene revealed that the polymer conformation remained unchanged upon addition of C60 while polymer induced fullerene aggregation was observed. 9 The resulting microstructure was shown to depend on the state of the solution and on the deposition technique (spin-coating vs drop-casting). Interestingly, the same behaviour was observed with phenyl-C61-butyric acid methyl ester (PCBM) in relatively poor solvent (toluene) but not in good solvent (chlorobenzene).…”
Section: Introductionmentioning
confidence: 99%